1986
DOI: 10.1007/bf01314285
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of actin-containing microfilaments in HSV-induced cytopathology and the influence of inhibitors of glycosylation

Abstract: Two and a half hours after infection with a high dose of different strains of HSV-1 which induce rounding of cells, breakdown of actin containing microfilaments can be observed. At the periphery of the cell, actin containing knob-like protuberances were visible. Later on, actin seems to be located exclusively on the surface of cells. Observations were done by immunofluorescence microscopy, scanning electron-microscopy and immunoperoxidase staining of ultrathin sections. The envelope of HSV appears to be staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…4A). Actin stress fibers are also largely depolymerized during infection (16,41,59,63). When infected Vero cells were stained for actin with Texas Red-labeled phalloidin, few stress fibers were visible but the actin cortex (the unbundled, highly branched actin lining the cell membrane) could still be seen in most cases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Actin stress fibers are also largely depolymerized during infection (16,41,59,63). When infected Vero cells were stained for actin with Texas Red-labeled phalloidin, few stress fibers were visible but the actin cortex (the unbundled, highly branched actin lining the cell membrane) could still be seen in most cases (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CV-1 cells were grown either on coverslips or in flasks at a density of 3 x 104 cells/cm 2 (Bachmann et al, 1989). The~, were infected with HSV-1 strains HFEM, Lenette or 17 syn ÷ or with temperaturesensitive (ts) mutants at high multiplicity (10 p.f.u,/cell) (Heeg et at., 1986;Metzger et al, 1988). The ts mutants were defective in either the immediate early (IE) protein (M~ 175K) (tsK) or in DNA synthesis (tsS) (Metzger et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…This cytopathology is characterized by (i) rounding up of cells caused by cytoskeletal destabilizations and loss of matrix binding proteins, (ii) nucleolar alterations and chromatin margination or damage, and (iii) an overall decrease in cellular macromolecular synthesis (5,25,26,55,57,58). Although cytolysis due to viral replication is generally believed to occur through a necrotic route, recent studies have indicated that one aspect of HSV-1-induced CPE is programmed cell death, or apoptosis (1,3,19,32,35).…”
mentioning
confidence: 99%